Dental caries in the primary dentition in public nursery school children in Juiz de Fora, Minas Gerais, Brazil Cárie dentária na dentição decídua de crianças assistidas em algumas creches públicas em Juiz de Fora, Minas Gerais, Brasil - Isabel Cristina Gonçalves Leite; Rosangela Almeida Ribeiro (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2000)
The aim of this study was to assess the prevalence of dental caries in the primary dentition and associated variables in low socioeconomic preschool children enrolled in public nursery schools in Juiz de Fora, Minas Gerais, Brazil. Four public institutions were selected by geographic criteria (two in the central region and two in the peripheral region). The study population comprised 338 children (181 boys; 157 girls) aged 2-6 years old. Dental caries was recorded using the decayed, missing, and filled teeth (dmf-t) index. Among the examined children, 50.6% were caries-free. The mean dmf-t index was 2.03. It was higher in the peripheral nursery schools (p < 0.01). A trend towards a difference between sexes (p = 0.06) was observed. Logistic regression analysis selected a previous child's visit to dentist (p < 0.001), geographic location of the public nursery school (p < 0.01), and age (p < 0.01) as predictive variables for the dmf-t index. The study showed the need for an oral health program for this population, including both curative and preventive measures in order to achieve the WHO/FDI goals for the year 2000, namely 50% of children free of caries at age 5-6 years. O objetivo deste estudo foi avaliar a prevalência de cárie dentária em dentição decídua e variáveis a ela associadas em pré-escolares, de baixo nível sócio-econômico, assistidos em creches públicas da cidade de Juiz de Fora, Minas Gerais, Brasil. Quatro instituições públicas foram selecionadas por critérios geográficos (duas na região central e duas na região periférica). A população do estudo compreendeu 338 crianças (181 meninos; 157 meninas) com idade de dois a seis anos. A cárie dentária foi registrada usando o índice ceo-d. Dentre as crianças examinadas, 50,6% estavam livres de cárie. A média do índice ceo-d foi 2,03, que foi maior na creches periféricas (p < 0,01), e uma tendência de diferença entre sexos foi observada (p = 0,06). A análise de regressão logística selecionou as variáveis visita prévia da criança ao dentista (p < 0,001), localização geográfica da creche pública (p < 0,01) e idade (p < 0,01) como preditoras do índice ceo-d. O estudo mostrou a necessidade de um programa de saúde bucal para essa população, incluindo medidas tanto curativas, quanto preventivas, com o objetivo de alcançar as metas da OMS/FDI para o ano 2000 (50% de crianças livres de cárie na faixa etária de cinco a seis anos).